Tantangan Dan Strategi Guru Dalam Mengimplementasikan Model Pembelajaran Problem Based Learning (Study Kasus Pembelajaran Di Kelas XII Muallimat Nwdi Kelayu) - Farhana Muhammad; Nadila Afriliana; Nuruzziadatul Jalilah; Sofyan Saori; M. Adnan Hidayat (CIRCULAR: Jurnal Pendidikan Sosial dan Ekonomi, 2025)
This study aims to analyze the challenges faced by teachers and the strategies used in implementing the Problem Based Learning (PBL) model in teaching and learning activities in class XII Mu’allimat NWDI Kelayu. PBL has long been seen as a learning approach capable of encouraging critical thinking skills, independent learning, and students' problem-solving abilities. However, its implementation in schools still faces various obstacles, both in terms of planning, implementation, and evaluation of learning. This study used a qualitative approach with a case study type. Data were collected through learning observations, in-depth interviews with teachers, and documentation of learning tools. The results showed that the main challenges included limited time to implement all stages of PBL, low initial student readiness in understanding problems, diversity of student abilities in group work, and limited media and learning support references. Nevertheless, teachers implemented a number of adaptive strategies such as simplifying problem scenarios, providing scaffolding, combining PBL with interactive lectures, and optimizing time management and group dynamics. These findings confirm that the success of PBL implementation is greatly influenced by teachers' creativity, flexibility, and ability to adapt the learning approach to classroom conditions. This study recommends the need to strengthen teacher competencies in problem design and discussion-based classroom management to increase the effectiveness of PBL implementation.